Monopoly Development Using QR Code Technology as A Science Learning Media on the Topic of Indonesian Biodiversity at SMP Negeri 27 Medan - Ali Ahmatul Umri Hasibuan; Khairiza Lubis; Koriatul Jannah Siregar; Al-Murizka Annisa; Sunita Karin Purba; Ghania Dhia Ulhaq Lubis (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
This research aims to develop a monopoly game integrated with QR Code technology as a science learning media on Indonesian biodiversity topic. The Monopoly media was designed to be suitable and effective for junior high school science courses, specifically at SMP Negeri 27 Medan. The development process follows the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model with data analysis techniques from validation sheets (content, media, and assessment) and teacher and student assessments presented in the form of a summary list using a likert scale (maximum 5 and minimum 1) which is then interpreted qualitatively. Validation results showed high feasibility scores of 85.38% from content experts, 91.54% from media experts, and 93.3% from assessment expert. Teacher responses also indicated the score average value of 90.62%, while student responses showed an overall feasibility score of 91.13%, with attractiveness receiving the highest rating at 93.12%.